Iron deficiency caused by intestinal iron loss: novel candidate genes for severe anemia - Huettmann, Carolina; Stelljes, Matthias; Sivalingam, Sugirthan; Fobker, Manfred; Vrachimis, Alexis; Exler, Anne; Wenning, Christian; Wempe, Carola; Penke, Matthias; Buness, Andreas; Ludwig, Kerstin U.; Muckenthaler, Martina; et al. (Genes, 2021)
The adult human body contains about 4 g of iron. About 1-2 mg of iron is absorbed every day, and in healthy individuals, the same amount is excreted. We describe a patient who presents with severe iron deficiency anemia with hemoglobin levels below 6 g/dL and ferritin levels below 30 ng/mL. Although red blood cell concentrates and intravenous iron have been substituted every month for years, body iron stores remain depleted. Diagnostics have included several esophago-gastro-duodenoscopies, colonoscopies, MRI of the liver, repetitive bone marrow biopsies, psychological analysis, application of radioactive iron to determine intact erythropoiesis, and measurement of iron excretion in urine and feces. Typically, gastrointestinal bleeding is a major cause of iron loss. Surprisingly, intestinal iron excretion in stool in the patient was repetitively increased, without gastrointestinal bleeding. Furthermore, whole exome sequencing was performed in the patient and additional family members to identify potential causative genetic variants that may cause intestinal iron loss. Under different inheritance models, several rare mutations were identified, two of which (in CISD1 and KRI1) are likely to be functionally relevant. Intestinal iron loss in the current form has not yet been described and is, with high probability, the cause of the severe iron deficiency anemia in this patient.